Applications of Molecular Diagnostic Testing in Food Allergy - Hoffmann-Sommergruber, Karin (Curr Allergy Asthma Rep, 2015)
IgE-mediated food allergy is a relevant health problem inducing symptoms ranging from mild local reactions up to severe life-threatening situations. Currently, no immunotherapy is available and avoidance of the incriminating food is the method of choice. Therefore, reliable diagnostic tools to formulate dietary recommendations and to avoid unnecessary exclusion diets for the individual patient are urgently needed. This review provides an update on the current knowledge on food allergens and their application in various diagnostic approaches such as skin prick test, basophil activation test, and serum IgE testing. Furthermore, these new approaches are discussed and compared to conventional extract-based assays and correlated to the gold standard of food allergy diagnosis, the double-blind placebo-controlled food challenge. Finally, the application of food allergens for preventive measurements such as allergen detection assays and the determination of threshold levels for allergen levels are discussed.